Inherited Nitrogen Distribution Control in Covalent Organic Framework Cathodes for Efficient Electrochemical Lithium Recovery via Capacitive Deionization - Rajesh Dhanushkotti; Abdul Khayum Mohammed; Kayaramkodath Chandran Ranjeesh; Hema Mylnahalli Krishnegowda; Najat Maher Aldaqqa; Dinesh Shetty (Advanced Science)
Abstract The economic recovery of lithium from brine generated by desalination plants presents a promising pathway toward achieving a sustainable water desalination economy. Selectively recovering Li+ ions from brine is challenging due to the presence of other dominant ions. While electrochemical separation techniques, such as hybrid capacitive deionization (HCDI), offer several advantages, success largely depends on developing suitable cathodes currently limited to inorganic materials with notable constraints. Herein, the potential of controlling heteroatom distribution within 2D covalent organic frameworks (2D‐COFs) is explored for electrochemical lithium recovery. This marks the first exploration of COF cathodes for lithium extraction via HCDI. By carefully modulating the density of heteroatoms within the framework backbone, this study aims to understand their critical role better and achieve efficient cathode materials. Notably, Tta‐Dfp, the representative COF, demonstrates a lithium recovery rate of 15.7 mg g⁻¹ at 1.4 V, with a Li‐ion concentration of 300 mg L⁻¹, and exhibits ∼80% selectivity for lithium extraction. At the same time, the device achieves 97.7% capacitance retention after 500 charge‐discharge cycles. Through controlled COFs, density functional theory (DFT) analysis, and post‐electrode characterizations, we elucidate the pivotal role of nitrogen distribution in lithium recovery.